Prehistoric men - Braidwood, Robert J. (Chicago : Scott, Foresman and Company, 1967)
Summary.
Prema predgovoru, 1. izd. u: Popular series.Anthropology / Field Museum of Natural History, Nr. 37, 1948.
Bibliografija: str. 171-175.
Kazalo.
Keywords: prapovijest; pračovjek; evolucija; razvoj čovjeka